2020
DOI: 10.1128/jvi.01879-19
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Flexibility in Respiratory Syncytial Virus G Neutralizing Epitopes

Abstract: Respiratory syncytial virus (RSV) is a top cause of severe lower respiratory tract disease and mortality in infants and the elderly. Currently, no vaccine or effective treatment exists for RSV. The RSV G glycoprotein mediates viral attachment to cells and contributes to pathogenesis by modulating host immunity through interactions with the human chemokine receptor CX3CR1. Antibodies targeting the RSV G central conserved domain are protective in both prophylactic and postinfection animal models. Here, we descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 75 publications
1
20
0
Order By: Relevance
“…The crystal structures of the broadly neutralizing human mAbs, 3G12 and 3D3, bound to RSV G protein CCD, have permitted the determination of interactions outside the linear epitope, revealing a role for a G protein cysteines in stabilizing conformational epitopes and contributing to high-affinity antibody binding [ 43 , 44 ]. The RSV G protein is important in RSV infection, as the G protein CCD contains a CX3C chemokine motif which facilitates binding to CX3CR1 [ 13 , 45 ], and CX3CL1 mimicry has been shown to facilitate RSV infection and alter CX3CL1-mediated chemotaxis of human and mouse leukocytes [ 10 , 13 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structures of the broadly neutralizing human mAbs, 3G12 and 3D3, bound to RSV G protein CCD, have permitted the determination of interactions outside the linear epitope, revealing a role for a G protein cysteines in stabilizing conformational epitopes and contributing to high-affinity antibody binding [ 43 , 44 ]. The RSV G protein is important in RSV infection, as the G protein CCD contains a CX3C chemokine motif which facilitates binding to CX3CR1 [ 13 , 45 ], and CX3CL1 mimicry has been shown to facilitate RSV infection and alter CX3CL1-mediated chemotaxis of human and mouse leukocytes [ 10 , 13 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most likely explanation for the importance of the CX3C motif is that the structural integrity of the site must be maintained. Recently, it has been demonstrated that maintaining the adjacent domains and the regional structure of the G protein is important for antibody production [ 73 ], too. Therefore, though protective non-neutralizing antibodies may target regions other than the central conserved domain, altering the CX3C motif could change the conformation of the G protein and thus make these epitopes unrecognizable to those antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…The RBD is structurally associated with the NTD of a neighboring chain 6,31 . Since the conformations of viral proteins can be altered significantly upon antibody binding 32,33 , the binding of enhancing antibodies to a specific site on the NTD may modulate the NTD-RBD interchain interaction, thus increasing the open conformation of RBD.…”
Section: Discussionmentioning
confidence: 99%